The complete book of sewing techniques : a practical guide to sewing, patchwork and embroidery shown in more than 900 step-by-step photographs - Wood, Dorothy (Lorenz Books, 2020)
This is the complete guide to sewing, patchwork and embroidery. Whether you are cutting out a pattern, turning hems or deciding which type of zipper or seam to use, concise instructions guide you through each stage, one step at a time.